2019
DOI: 10.1002/bes2.1562
|View full text |Cite
|
Sign up to set email alerts
|

Bedrock Nitrogen Weathering Stimulates Biological Nitrogen Fixation

Abstract: Global ecosystem models suggest that bedrock nitrogen (N) weathering contributes 10-20% of total N inputs to the natural terrestrial biosphere and >38% of ecosystem N supplies in temperate forests specifically. Yet, the role of rock N weathering in shaping ecological processes and biogeochemical fluxes is largely unknown. Here, we show that temperate forest ecosystems underlain by N-rich bedrock exhibit higher free-living N fixation rates than similar forests residing on N-poor parent materials, across sites e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Moreover, from a preindustrial perspective, both rock N and weathering fluxes have been important over geo‐evolutionary time scales, and so future studies attempting to dissect the impacts of the two N inputs will need to carry out simulations in long model spin‐up cycles. Although much more work is needed, there is evidence that increased supply of N from bedrock weathering stimulates biological N fixation through feedbacks in the C cycle (Dynarski et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, from a preindustrial perspective, both rock N and weathering fluxes have been important over geo‐evolutionary time scales, and so future studies attempting to dissect the impacts of the two N inputs will need to carry out simulations in long model spin‐up cycles. Although much more work is needed, there is evidence that increased supply of N from bedrock weathering stimulates biological N fixation through feedbacks in the C cycle (Dynarski et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Ecosystem models have highlighted the potential for progressive nitrogen limitations of plant productivity to emerge; yet studies have found mixed results and the terrestrial CO 2 sink continues to occur at ∼2 Gt C/yr, or ∼25% of global C emissions from human activities. Past studies have identified an important role for rock nitrogen weathering in nutrient cycles, ecological interactions, and regional carbon sequestration patterns across forests (Dynarski et al., 2019; Houlton & Morford, 2015; Morford et al., 2011), which could affect the nature and pattern of N limitation. Despite the evidence that rock weathering accounts for 26% of preindustrial N inputs, at the scale of the ecosystem, region and global, (Houlton et al., 2018), this pathway of N input has not been examined in global carbon‐climate‐nutrient models.…”
Section: Introductionmentioning
confidence: 99%
“…For example, low rates of rock N weathering can select for symbioses between plants and mycorrhizal fungi, which secrete enzymes to obtain organic N as well as stimulate rock weathering (Koele, Dickie, Blum, Gleason, & Graaf, ). Recent work by Dynarski, Morford, Mitchell, and Houlton () has shown that low rates of rock N weathering in locations with N‐poor parent materials are associated with reduced C storage and soil P retention, which thereby impedes BNF and potentially in the long term reinforces selection for symbioses between plants and mycorrhizal fungi. Conversely, C gains in forests residing on N‐rich geological substrates can enhance BNF rates via free‐living microbes in litter, a result that contrasts with natural and simulated anthropogenic N deposition (Dynarski et al, ).…”
Section: Ecological and Evolutionary Significance Of Rock N Weatheringmentioning
confidence: 99%
“…Recent work by Dynarski, Morford, Mitchell, and Houlton () has shown that low rates of rock N weathering in locations with N‐poor parent materials are associated with reduced C storage and soil P retention, which thereby impedes BNF and potentially in the long term reinforces selection for symbioses between plants and mycorrhizal fungi. Conversely, C gains in forests residing on N‐rich geological substrates can enhance BNF rates via free‐living microbes in litter, a result that contrasts with natural and simulated anthropogenic N deposition (Dynarski et al, ). Thus, N‐rich geological substrates should select for plants that have high capacities for N uptake and use, both directly through increased rock N weathering and indirectly through enhanced BNF.…”
Section: Ecological and Evolutionary Significance Of Rock N Weatheringmentioning
confidence: 99%
“…N inputs are mainly from Biological Nitrogen Fixation (BNF) and atmospheric deposition with little addition from rock weathering (Du et al , 2020) There are two types of nitrogen deposition from the atmosphere: wet (precipitation) and dry (particles). Among the two, wet deposition represents most of the atmospheric nitrogen input (Fowler et al , 2013;Dynarski et al , 2019). In contrast, the main input of P comes from rock weathering (mainly apatite) with lesser inputs from atmospheric deposition as dust particles.…”
Section: Introductionmentioning
confidence: 99%